Pengaruh Komunikasi Visual Dalam Kampanye Lomba Pendidikan Di Media Sosial Instagram - Willy Widinia Widi; Aa Ridwan Maulana Sya'bani; Maulana Maulana; Mochammad Daffa; Nazirah Naswa; Muhammad Ihsan Hadi Surya; Muhammad Ripaldi; Ali Alamsyah Kusumadinata (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
This study examines the effectiveness of an educational competition campaign conducted through Instagram, focusing on the role of visual communication in building audience interest and participation. Using a mixed-method approach combining qualitative and quantitative analysis, the findings reveal that the visual communication strategy successfully created high engagement and encouraged active participation. The analysis demonstrates that visual quality has a significant positive influence on audience interest, although aspects of visual appeal still require enhancement for optimal results. The study concludes that integrating strong visual elements with relevant content and persuasive narratives is key to the success of educational campaigns on social media platforms.